2008
DOI: 10.1097/mph.0b013e318165b298
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Stress Testing in Children With Sickle Cell Disease Who are on Long-term Erythrocytapheresis

Abstract: The purpose of the study was to assess the feasibility and safety of symptom-limited cardiopulmonary stress testing (CPST) in children with sickle cell disease (SCD), who are on long-term erythrocytapheresis. Maximal symptom-limited CPST was performed in 16 children with SCD who were maintained on long-term erythrocytapheresis and the exercise response in this patient cohort was compared with those of a healthy control population. All patients completed the CPST without any complications. Twelve patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…In the exchange transfusion experiment attempting to keep Hgb the same (but actually Hgb increased by 1.4 g/dL), the effect of Hgb A was directly queried and results suggested improved exercise capacity was associated with Hgb A 21 . In contrast, in a study of children on long‐term exchange transfusion maintaining Hgb S approximately 30%, average peak VO 2 was still less than 80% compared to healthy controls, but the transfused patients also had significantly lower Hgb (9.3 ± 0.5 g/dL) than healthy controls 32 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the exchange transfusion experiment attempting to keep Hgb the same (but actually Hgb increased by 1.4 g/dL), the effect of Hgb A was directly queried and results suggested improved exercise capacity was associated with Hgb A 21 . In contrast, in a study of children on long‐term exchange transfusion maintaining Hgb S approximately 30%, average peak VO 2 was still less than 80% compared to healthy controls, but the transfused patients also had significantly lower Hgb (9.3 ± 0.5 g/dL) than healthy controls 32 …”
Section: Discussionmentioning
confidence: 99%
“…21 In contrast, in a study of children on long-term exchange transfusion maintaining Hgb S approximately 30%, average peak VO 2 was still less than 80% compared to healthy controls, but the transfused patients also had significantly lower Hgb (9.3 ± 0.5 g/dL) than healthy controls. 32 Several studies documented improved exercise performance in SCA patients after moderate exercise training.…”
Section: Improving Exercise Capacity In Sca Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…[43] In the literature, only a few pediatric studies have compared the aerobic capacity of children and adolescents with sickle cell disease with healthy controls. [10,29,44] These studies investigated the exercise oxygen extraction physiology of anemic patients on submaximal CPET [44] and the safety of CPET in children with sickle cell disease [29]. In a controlled prospective study, Liem et al reported a VO 2max difference of 10.1 mL/kg/min between 60 children with sickle cell disease (BMI = 21 ± 4 kg/m2) and 30 controls (BMI = 24 ± 7 kg/m 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…This will cause a sluggish flow of the blood in the small vessels. Subsequently, will lead to malvascularization of the body tissues and organs that causes tissue hypoxia, vaso-occlusive crisis (VOC), organ failure and severe anemia [2,3].…”
Section: Introductionmentioning
confidence: 99%